2016
DOI: 10.21577/0100-4042.20160123
|View full text |Cite
|
Sign up to set email alerts
|

Sistemas carreadores lipídicos nanoestruturados para ivermectina e metopreno visando controle de parasitas

Abstract: CONTROL. The study of characteristics of nanoscale structures and applications now has great interest of researchers from different areas. In this regard, lipid carriers can improve the bioavailability of drugs and the reduction of possible toxicological effects. Thus, the development of nanostructured systems for the agricultural sector, aimed at combating parasites may reduce extensive damage caused to livestock producers and animal health. This study aimed to prepare and characterize lipid carrier systems, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…The obtained results indicated that encapsulated IVM had a benefit of delivering its therapeutic property in the cytoplasm without being degraded via endosome/lysosome 59 . Also, the cytocompatibility of IVM encapsulated lecithin/PMMA nanoparticles had not yet been reported in the literature, and it was superior to carrier systems reported in other studies 60 …”
Section: Resultsmentioning
confidence: 78%
“…The obtained results indicated that encapsulated IVM had a benefit of delivering its therapeutic property in the cytoplasm without being degraded via endosome/lysosome 59 . Also, the cytocompatibility of IVM encapsulated lecithin/PMMA nanoparticles had not yet been reported in the literature, and it was superior to carrier systems reported in other studies 60 …”
Section: Resultsmentioning
confidence: 78%
“…Nota-se que no decorrer do tempo o pH diminui em algum momento para todas as formulações (Figura 2). Cola e colaboradores (2016) [14] no desenvolvimento de CLN demonstrou também uma tendência do pH diminuir ao longo do tempo quando comparado às NLS que demonstram o contrário. As variações podem estar relacionadas a degradação do princípio ativo ou dos constituintes da formulação devido à hidrólise química.…”
Section: Caracterização Do Clnunclassified
“…CLN desenvolvidas com óleo de copaíba para o carreamento de extrato de Curcuma longa por SILVA (2017) [19] apresentaram um diâmetro médio próximo de 200 nm, de modo que as formulações desenvolvidas neste trabalho apresentam valores semelhantes aos descritos na literatura quanto a encapsulação do óleo de copaíba, utilização de manteigas vegetais e a nanoencapsulação de pesticidas botânicos. As CLN apresentam um tamanho de partícula menor comparado às NLS devido a sua composição lipídica líquida e sólida, já que lipídios com o ponto de fusão maior podem elevar o tamanho de partícula [14]. Os parâmetros analisados dos CLN são frequentemente determinados para caracterizar sistemas nanométricos, porque estas características irão ter grande influência sobre a estabilidade e eficiência biológica dos ativos, inclusive nas preparações pesticidas [20].…”
Section: Caracterização Do Clnunclassified
“…These nanodevices were employed to study the effect of ivermectin as an antiparasitic agent or against microfilaria and scabies. [12][13][14][15][16][17][18][19][20] However, most of these nanomaterials lack detailed characterization, targeted delivery to a specific site, or antiviral activity (Table S1). Additionally, there is low IVM loading in these NPs which typically are large in size, limiting their translation to therapeutic use.…”
mentioning
confidence: 99%